Redescription of Philometra globiceps (Rudolphi, 1819) (Nematoda: Philometridae), the type species of Philometra Costa, 1845, including the first data obtained by SEM - Moravec, František; Tedesco, Perla (Parasitology research, 2015)
A redescription of Philometra globiceps (Rudolphi 1819), the type species of Philometra Costa 1845 (Philometridae), is provided on the basis of specimens collected from the gonads, stomach, pyloric caeca, intestine and gallbladder of the marine fish Uranoscopus scaber Linnaeus (Uranoscopidae, Perciformes) caught in the Ionian Sea off Ugento, southern Italy. Light microscopical and scanning electron microscopical examinations (latter used for the first time in this species) of the specimens revealed some previously unreported morphological features, such as the location of submedian pairs of cephalic papillae of external circle on four elevated cuticular lobes in gravid females, the presence of amphids, genital papillae and phasmids in males, the lamellate structure of the distal end of gubernaculum appearing as a dorsal protuberance in lateral view and the structure of the male caudal end. A taxonomically important feature of P. globiceps is the details in the dorsal transverse lamella-like structures on the distal end of the gubernaculum, by which this species can be separated from other gonad-infecting species of this genus. Apparently, P. globiceps is a specific parasite of U. scaber and all previous records of this species from hosts belonging to other fish families are evidently based on misidentifications.
Keywords: Italy; Microscopy, Electron, Scanning; Parasitic nematode; Spirurida Infections; Uranoscopus; cékum; Dracunculoidea; mikroskopie elektronová rastrovací; infekce hlísticemi řádu Spirurida; mužské pohlaví; Stomach; Marine fish; Gonads; gonády; žaludek; ženské pohlaví; zvířata; nemoci ryb; Itálie; Fish Diseases; Perciformes; Cecum; Female; Male; Animals